Analysis of forward scattering of an acoustical zeroth-order Bessel beam from rigid complicated (aspherical) structures. (October 2017) - Li, Wei; Chai, Yingbin; Gong, Zhixiong; Marston, Philip L.
Highlights: Forward scattering from rigid complicated shapes in a Bessel beam is considered. The T-matrix method is applicable to structures with large aspect ratios. Geometrical ray diagrams and optical theorem reveal scattering mechanisms in ABB. The concepts of local/total forward scattering from ABB are proposed and discussed. Abstract: The forward scattering from rigid spheroids and endcapped cylinders with finite length (even with a large aspect ratio) immersed in a non-viscous fluid under the illumination of an idealized zeroth-order acoustical Bessel beam (ABB) with arbitrary angles of incidence is calculated and analyzed in the implementation of the T -matrix method (TTM). Based on the present method, the incident coefficients of expansion for the incident ABB are derived and simplifying methods are proposed for the numerical accuracy and computational efficiency according to the geometrical symmetries. A home-made MATLAB software package is constructed accordingly, and then verified and validated for the ABB scattering from rigid aspherical obstacles. Several numerical examples are computed for the forward scattering from both rigid spheroids and finite cylinder, with particular emphasis on the aspect ratios, the half-cone angles of ABBs, the incident angles and the dimensionless frequencies. The rectangular patterns of target strength in the ( β, θ s ) domain (where β is the half-cone angle of the ABB and θ s is the scattered polar angle) and local/total forward scattering versus dimensionless frequency are exhibited, which could provide new insights into the physical mechanisms of Bessel beam scattering by rigid spheroids and finite cylinders. The ray diagrams in geometrical models for the scattering in the forward half-space and the optical cross-section theorem help to interpret the scattering mechanisms of ABBs. This research work may provide an alternative for the partial wave series solution under certain circumstances interacting with ABBs for complicated obstacles and benefit some related works in optics and electromagnetics.